The Social Cost of Optimal Taxes in an Imperfectly Competitive Economy - Sheikh Selim (Cardiff University, Cardiff Business School, 2005)
In this paper we calibrate the social cost of optimal taxes in a class of imperfectly competitive economies and examine the correspondence of this social cost with the number of tax instruments and the number and the sources of distortions. We calibrate the Ramsey equilibrium for three standard models of imperfect competition. These settings are different in number of sources of market distortion and number of tax instruments. Our calibration clearly shows that optimal taxes in an imperfectly competitive economy incur lower social cost than those in a competitive economy, implying that they are generally more efficient as competition enhancing policy tools. We find that optimal taxes in our models can cost up to 48% less forgone consumption relative to those in a competitive market economy.
Keywords: D42; E62; H21; H30; 330; Optimal taxation; Ramsey Problem; Welfare Cost